Rijal al-Hadis dan al-Jarh wa al-Ta’dil: Kajian Metodologi Penilaian Kualitas Perawi Hadis - Indra Yuliasti; Muhammad Saleh; Subehan Halik; Muhammad Yahya; Indra Yuliasti, Indra Yuliasti (Lentera Jurnal, 2025)
This article aims to understand the science of Rijal al-Hadith and al-Jarh wa al-Ta'dil in an easy-to-understand way, as well as serve as a crucial test tool to assess the quality of the narrator of the hadith in terms of weaknesses (jarh) and excellence (ta'dil). The approach used in this study is a literature study, which involves an in-depth search and analysis of various related literature. The studies found in an effort to understand Rijal al-Hadith and al-Jarh wa al-Ta'dil include several important points that are systematic. First, the discussion begins with the basics of the science of Jarh wa Ta'dil, which includes its terminological and etymological definition, its strong theological-rational foundation in maintaining the authenticity of Islamic teachings, and the history of its development from the early days of Islam to become an established discipline. Furthermore, this article also outlines the levels of Jarh wa Ta'dil itself, which are vital in determining the degree of credibility of a hadith narrator. By comprehensively understanding these fundamental aspects, it is hoped that readers will not only gain theoretical knowledge, but also be able to better appreciate the importance of the role of Rijal al-Hadith and al-Jarh wa al-Ta'dil in contemporary hadith studies. This understanding will increase awareness of how the process of carefully assessing the narrator of the hadith can directly influence and guarantee the validity and authority of a hadith in the broad and complex Islamic scientific tradition. This confirms the strategic position of the two sciences as guardians of the purity of the teachings of the Prophet Muhammad SAW.